A One Session Gait Retraining Protocol with Metronome Augmentation Increases Cadence in Novice and Recreational Runners - Angie Huber; Dave Verhoff (North American Sports Medicine Institute, 2024)
# Background Running is a common leisure physical activity that carries a risk for running related injury (RRI). Non-experienced runners are more likely to sustain RRIs. One form of gait retraining focuses on increasing cadence to improve running biomechanics related to RRI. Protocols for increasing cadence must be pragmatic to be implemented into clinical practice. # Hypothesis/Purpose The purpose of this study was to determine if a pragmatic protocol including one instructional session, followed by independent gait retraining with metronome augmentation resulted in increased cadence and altered biomechanics in novice and recreational runners. # Study Design Randomized Controlled Trial # Methods Thirty-three novice or recreational adult runners completed a 12 Minute Cooper Run on an indoor track. Variables measured during the 12 Minute Cooper Run included distance, rate of perceived exertion (RPE), heart rate (HR), and 3-D biomechanics using inertial measurement units (IMUs). After baseline testing, the intervention group received instruction and five minutes of gait retraining at a cadence set 5-10% higher than baseline with metronome augmentation (Pro Metronome- Tempo, Beat; by Xiao Yixiang). They then ran two to three times a week for two weeks up to 30 minutes per session with the metronome set at the new cadence. After two weeks, repeat testing using the same protocol was completed. A Mann-Whitney U test analyzed differences between groups. # Results Cadence at one minute (p = 0.037) and average cadence over the entire run (p=0.002) increased in the intervention group only with a large effect size (Cohens *d* = 0.837). No other group differences were found. # Conclusion A pragmatic gait retraining protocol with metronome augmentation including one instructional and four to six independent sessions over a two-week duration increased cadence without negative effects on HR, RPE, distance. Biomechanics did not change with this intervention. Further research with pragmatic gait retraining protocols that increase cadence are needed with larger sample sizes, repeated measures over time, across runners of various abilities and experience levels. # Level of Evidence Level 2